Response of Mixed-Phase Cloud Microphysics to Aerosol Perturbations at the Contrasting Sites of Limassol, Cyprus, and Punta Arenas, Chile - He, Yun; Seifert, Patric; Jimenez, Cristofer; Radenz, Martin; Ansmann, Albert; Bühl, Johannes; Mamouri, Rodanthi-Elisavet; Barja Gonzalez, Boris (My University, 2025)
Ice crystal number concentrations (ICNC) of shallow stratiform mixed-phase clouds (MPCs) were contextualized with the ice nucleating particle concentrations (INPC) of the same airmass in which the cloud layers formed. Prerequisite are ground-based lidar and cloud radar observations from two sites with contrasting aerosol conditions: Limassol (34.67 (Formula presented.) N, 33.04 (Formula presented.) E), Cyprus, dominated by desert dust and continental aerosols, and Punta Arenas (53.13 (Formula presented.) S, 70.88 (Formula presented.) W), Chile, where marine aerosol and a so far unquantified fraction of aerosol from other sources prevails. For each MPC case, cloud-level INPC is derived from lidar observations of the cloud-free surroundings. The ICNC nucleated within the MPC is derived 180 m below the liquid-dominated cloud-top layer based on the synergetic observations from lidar and radar. At Limassol, both ICNC and INPC in dust-embedded MPC range from 0.05 to 3 L−1 and show good correlation. At similar temperatures, INPC derived in the free troposphere above Punta Arenas are at least one order of magnitude lower than at Limassol. In contrast, an agreement between ICNC (0.02–2 L−1) and INPC (0.01–0.1 L−1) at temperatures below (Formula presented.) (Formula presented.) C is not observed at Punta Arenas. Given the previously demonstrated reliability of the ICNC retrieval, we suggest that current parameterizations of free-tropospheric INPC at temperatures below (Formula presented.) (Formula presented.) C in the Southern Hemisphere midlatitudes might lack relevant components, due to scarcity of long-term in situ data sets of INPC at these conditions. Despite the identified discrepancies for Punta Arenas, our study highlights the crucial role of ice-nucleating particles in the primary ice formation of shallow stratiform MPCs.
Keywords: aerosol-cloud interaction; cloud radar; ice crystal; ice-nucleating particle; lidar; mixed-phase cloud